Teenage pregnancy and mental health beyond the postpartum period: a systematic review. Issue 6 (8th February 2018) - Xavier, Chloé; Benoit, Anita; Brown, Hilary K
Abstract : Background: Teenage mothers are at increased risk for adverse social outcomes and short-term health problems, but long-term impacts on mental health are poorly understood. The aims of our systematic review were to determine the association between teenage pregnancy and mental health beyond the postpartum period, critically appraise the literature's quality and guide future research. Methods: We systematically searched MEDLINE, Embase, PsycINFO, CINAHL, Scopus and Web of Science from inception to June 2017 for peer-reviewed articles written in English or French. Data were collected using a modified Cochrane Data Extraction Form. Study quality was assessed using the Effective Public Health Practice Project critical appraisal tool. Heterogeneity of studies permitted only a qualitative synthesis. Results: Nine quantitative studies comprising the results from analyses of 11 cohorts met our criteria and were rated as strong (n=5), moderate (n=2) or weak (n=2). Three cohorts found a statistically significant association between teenage pregnancy and poor long-term mental health after adjustment, three found a statistically significant association before but not after adjustment and five did not find a statistically significant association. Studies observed varying degrees of attenuation after considering social context. Studies with statistically significant findings tended to comprise earlier cohorts, with outcomes measured at older ages. Conclusions: The association between teenage pregnancy and mental health beyond the postpartum period remains unclear. Future studies should employ age–period–cohort frameworks to disentangle effects of normative patterns and stress accumulation. Social factors are important in determining long-term mental health of teenage mothers and should be prioritised in prevention and intervention strategies.